Awareness, acceptability, congruency, and attainability of an academic institution’s vision, mission, goals, and objectives - Chriselda Saniata G. Niala; Dahlee S. Pascua (International Journal of Evaluation and Research in Education (IJERE), 2024)
The mandate of Isabela State University is to deliver higher learning in the arts, agriculture, natural sciences, technology, and specialized disciplines. Hence, the institution executes a strategic vision, mission, goals, and objectives (VMGO) to meet the expectations of its stakeholders. This research examined the degree of stakeholders’ awareness, acceptance and understanding of the Isabela State University, College of Business, Accountancy, and Public Administration’s (ISU-CBAPA) VMGO; its congruence with the educational approaches of the faculty and resources of the institution in delivering quality education; and whether the program goals and objectives of the business programs were attained. A quantitative descriptive research method was used. The results indicate that the respondents are generally highly aware of the ISU-CBAPA VMGO and its dissemination. The respondents perfectly understand and accept the ISU-CBAPA VMGO and highly perceive the extent of its congruence with academic strategies, practices, and activities. In addition, all respondents perceived that the ISU-CBAPA VMGO is being realized and favorably attained, despite the significant differences found. Recommendations include intensifying VMGO dissemination to external stakeholders, emphasizing VMGO commitments toward its realization, and emphasizing improvement on the students’ development of professional skills, research capabilities, and competencies, and their readiness for employment and/or managing a business.